Pelatihan Holistik Peningkatan Kompetensi Pedagogik Guru PAUD dalam Mengembangkan Pembelajaran Berbasis Proyek - Aufa, Nauwal; Zaratuzar, Zaratuzar (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This community service program aims to enhance the pedagogical competence of early childhood education (ECE) teachers through a holistic training focused on developing Project-Based Learning (PjBL). Project-Based Learning is recognized for encouraging active, creative, and critical thinking skills in young children. The training was designed comprehensively, covering theoretical understanding, project planning, and real-life implementation practices. Methods used included interactive lectures, case studies, group discussions, and field-based practicum. The activity was carried out at PAUD Bungong Jumpa, involving 10 ECE teachers. Evaluation results indicated a significant improvement in teachers’ understanding and skills related to PjBL implementation, as well as increased confidence in designing innovative and enjoyable learning experiences for young learners. This program demonstrates that holistic, practice-based training can be an effective strategy to improve the quality of education at the early childhood level.